Interactive Integrated Science Module with Coastal Tourism Context: A Feasibility Study on Students’ Scientific Literacy - Yamin Yamin; Sunu Wahyudhi; Dimas Pemilwan Putu Praja; Mohammad Adrio Syahbana Al Jabbar (Universitas Muhammadiyah Sidoarjo, 2026)
This study was conducted in response to the limited utilization of local potential as a contextual learning resource in junior high school science instruction. The research aimed to develop an interactive science module integrated with the theme of Madura coastal tourism and to examine its feasibility for junior high school science learning. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The development process was based on observations conducted at several coastal tourism sites in Madura, including Lobuk Beach and Siring Kemuning Beach in Bangkalan, as well as Nepa Monkey Forest Beach and Loan Malang Beach in Sampang. Data were collected through expert validation instruments involving subject matter experts and media experts. The feasibility of the developed module was analyzed using descriptive quantitative techniques. The validation results showed that the interactive science module achieved a feasibility score of 95.50% from the subject matter expert and 94.88% from the media expert, both categorized as very feasible. These findings indicate that the developed module is pedagogically and technically appropriate for use as a contextual science learning resource in junior high schools. The integration of Madura coastal tourism into science learning provides meaningful local-context content and may support the development of context-based science learning experiences.